Development of electrochemical sensor based on silica and silica/gold nanoparticle electrode for detection of arsenic (III) - Ismail, Suhainie (2017)
Electrochemical sensor for the detection of arsenic(III) has been successfully developed based on nanoparticles modified screen printed carbon electrode (SPCE). In this research, silica nanoparticles (SiNPs) and gold nanoparticles (AuNPs) were used as a modifier to enhance the performance of disposable screen printed carbon electrode. The electrocatalytic responses of the SiNPs and SiNPs/AuNPs modified electrode for the detection of As(III) were measured using cyclic voltammetry (CV) and linear sweep anodic stripping voltammetry (LSASV). The screen printed carbon electrode was modified by drop casting the nanoparticles onto the working electrode. There are two types of modified electrode were developed for detection and quantification of As(III) ions. Firstly, SiNPs/SPCE electrode was prepared by casting the SiNPs onto the SPCE surface. Meanwhile, AuNPs/SiNPs/SPCE electrode was prepared by casting the SiNPs onto the working electrode, and then layered with 3- mercaptopropionic acid (MPA) followed by attachment of AuNPs. Both modified electrode, SiNPs/SPCE and AuNPs/SiNPs/SPCE were then applied for As(III) detection. Electrochemical studies using LSASV performed with SiNPs/SPCE and AuNPs/SiNPs/SPCE were found to give a better response through the optimization of numerous analytical parameters. The detection of As(III) using SiNPs/SPCE showed a linear response towards different concentration of As(III) and linear calibration curve with R2 = 0.9702 was obtained. The detection limit of 5.64 µg L-1 was achieved by applying deposition potential of - 0.5 V and deposition time of 120 s. Meanwhile, the detection of As(III) using AuNPs/SiNPs/SPCE gave a linear response towards different concentration of As(III) and linear calibration curve with R2 = 0.9975 was obtained. The detection limit of 1.4 µg L-1 was achieved by applying deposition potential of - 0.4 V and deposition time of 120 s. The modified SPCE was characterized using Field Emission Scanning Electron Microscope (FESEM), Transmission Electron Microscope (TEM), and Energy Dispersive X-ray (EDX) respectively. The proposed methods showed good selectivity of target analyte even in the presence of some foreign ions. Furthermore, the developed sensors; SiNPs/SPCE and AuNPs/SiNPs/SPCE showed good reproducibility for six measurements where the RSD values of 5.72 % and 4.52 % were obtained, respectively.